Design and development of a smart window blind controlling system - Bhuiyan, Moinul; Mustaffa Kamal, Dzul Asyraff Firdhaus (2014)

(untitled)
The idea was conceived while watching television and always having to get up and adjust the blind because of the glare from the sun. A smart window blind system provides the correct amount of sunlight shine into the room. There are two settings the user can select via a switch: manual or automatic. Manual mode activates two push buttons for the tilting control. For automatic mode, the blind will open or close, depending on the amount of light that is shining into the window.  The blind will be fully closed when the light level is below 200, opened to 50% from maximum angle when it is above 800 and fully opened whenever the light level is between 200 and 800. A servo motor attached to a blind’s controlling shaft for the actuation of tilting.